Disentangling sources of variation in SSU rDNA sequences from single cell analyses of ciliates: impact of copy number variation and experimental error. Issue 1859 (26th July 2017) - Wang, Chundi; Zhang, Tengteng; Wang, Yurui; Katz, Laura A.; Gao, Feng; Song, Weibo
Abstract : Small subunit ribosomal DNA (SSU rDNA) is widely used for phylogenetic inference, barcoding and other taxonomy-based analyses. Recent studies indicate that SSU rDNA of ciliates may have a high level of sequence variation within a single cell, which impacts the interpretation of rDNA-based surveys. However, sequence variation can come from a variety of sources including experimental errors, especially the mutations generated by DNA polymerase in PCR. In the present study, we explore the impact of four DNA polymerases on sequence variation and find that low-fidelity polymerases exaggerate the estimates of single-cell sequence variation. Therefore, using a polymerase with high fidelity is essential for surveys of sequence variation. Another source of variation results from errors during amplification of SSU rDNA within the polyploidy somatic macronuclei of ciliates. To investigate further the impact of SSU rDNA copy number variation, we use a high-fidelity polymerase to examine the intra-individual SSU rDNA polymorphism in ciliates with varying levels of macronuclear amplification: Halteria grandinella, Blepharisma americanum and Strombidium stylifer . We estimate the rDNA copy numbers of these three species by single-cell quantitative PCR. The results indicate that: (i) sequence variation of SSU rDNA within a single cell is authentic in ciliates, but the level of intra-individual SSU rDNA polymorphism varies greatly among species; (ii) rDNA copy numbers vary greatly among species, even those within the same class; (iii) the average rDNA copy number of Halteria grandinella is about 567 893 (s.d. = 165 481), which is the highest record of rDNA copy number in ciliates to date; and (iv) based on our data and the records from previous studies, it is not always true in ciliates that rDNA copy numbers are positively correlated with cell or genome size.